The History Behind Badano Grand Mosque - Afriza Ningsih; Kotrini Kotrini (Politeknik Negeri Padang, 2017)
The History behind Badano Grand Mosque” is the history of an old mosque in Pariaman-West Sumatera. It is one of important information that needs to be shared to listeners as source of sharing information. There are a lot of old mosques still exist nowadays in West Sumatera but Badano Grand Mosque still has some interesting and uniques stories that make people in Pariaman are very proud of it. The radio feature of History behind Badano Grand Mosque will be able to attract a lot of tourists to visit this place. There are three procedures in making this project are conducted: Pre-production, Production, and Post-production. The main point of this project is production process. In production stage, there are some steps that were done such as doing interview with informants, choosing the insert, writing the script and recording the voice. The result of this project is an English script with 750 words.